A Theory of Conservative Revivals - Murat Iyigun; Jared Rubin; Avner Seror (Institute of Labor Economics (IZA), 2018)
Why do some societies fail to adopt more efficient political and economic institutions in response to changing economic conditions? And why do such conditions sometimes generate conservative ideological backlashes and, at other times, progressive social and political movements? We propose an explanation that highlights the interplay - or lack thereof - between productivity, cultural beliefs and institutions. In our model, production shocks that benefit one sector of the economy may induce forward-looking elites to provide public goods associated with a different, more traditional sector that benefits their interests. This investment results in more agents generating cultural beliefs complementary to the provision of the traditional good, which in turn increases the political power of the traditional elite. Hence, productivity shocks in a more advanced sector of the economy can increase investment, political power, and cultural capital associated with the more traditional sector of the economy, in the process generating a revival of beliefs associated with an outdated economic environment.
Keywords: D02; N40; N70; O33; O38; O43; Z10; 330; institutions; conservatism; cultural beliefs; cultural transmission; institutional change; technological change